Neelakurinji: A spectacular flower of Western ghats - Kamath, Shantesh Ramesh; M, Girish P; Panigrahi, Saipriya; Namita; Panwar, Sapna (Indian Horticulture, 2023)
The Neelakurinji, scientifically known as Strobilanthes spp. is a purplish flowering shrub, which blooms once in 12 years in the hills of the Western Ghats and Himalayan hills. The entire hill range looks blue once the blooming starts and retains for nearly three months. This unique lifecycle of the plant makes the hills a must-visit destination for travellers, botanists and nature enthusiasts. We must consider the Neelakurunji blooms as one of the wonders of the world and the heritage of our own Western Ghats. This article throws light on the significance, habitat, distribution and conservation status of Neelakurunji of Western Ghats.